2014
DOI: 10.1016/j.jnucmat.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydration and thermal treatment on ceria surface using non-intrusive techniques

Abstract: International audienceThe evolution of plutonium dioxide surface due to water adsorption seems to influence H-2 generation through the radiolysis of adsorbed water. Surface evolution of ceria, a non-radioactive surrogate for plutonium dioxide, was investigated using Inverse Gas Chromatography (IGC), Raman spectroscopy, Environmental Scanning Electronic Microscopy (ESEM) and Atomic Force Microscopy (AFM). IGC highlights the complexity of ceria surface revealing three different adsorption sites on surface and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…24 It was found that the Ce(IV) complexes have comparable behaviors in term of structures, charge distribution and stabilities to those of Pu(IV), and that Ce(IV) is a priori a better surrogate for Pu(IV) for experimental studies than Th(IV) or U(IV). This conclusion is in line with the observed applicability of cerium dioxide CeO 2 as a surrogate for plutonium dioxide PuO 2steaming from their structural similarities and comparable redox behavior [64][65][66][67].…”
supporting
confidence: 81%
“…24 It was found that the Ce(IV) complexes have comparable behaviors in term of structures, charge distribution and stabilities to those of Pu(IV), and that Ce(IV) is a priori a better surrogate for Pu(IV) for experimental studies than Th(IV) or U(IV). This conclusion is in line with the observed applicability of cerium dioxide CeO 2 as a surrogate for plutonium dioxide PuO 2steaming from their structural similarities and comparable redox behavior [64][65][66][67].…”
supporting
confidence: 81%
“…Particularly, cerium dioxide has been largely investigated in the replacement of plutonium dioxide due to structural similarities and comparable redox behavior. [40][41][42][43][44] CeO 2 crystallizes in the fluorite-type structure (Fm3 ˉm space group) and exhibits close lattice parameters with a similar octacoordinated ionic radius (Ce 4+ = 0.97 Å and Pu 4+ = 0.96 Å). 45 Also, cerium can exist under +III and +IV oxidation states, in solid or in liquid media, which is very interesting to simulate PuO 2 behavior during reducing or complexing dissolutions.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of Raman spectra (Fig. 6) of the Si substrate obtained by its successive dipping at first into the 3% H 2 O 2 solution for 30 sec and then into the Ce(NO 3 ) 3 and Mohr's salt solution has shown that besides the Fe-O stretching vibrations (221 and 287 cm −1 ) in iron (III) oxide-hydroxide [31, 32] and Ce-O stretching vibrations (402 and 490 cm −1 ) in cerium (II) oxide-hydroxide [17, 33], the mode at 830 cm −1 attributed to the stretching vibrations of Ce-O 2 - peroxide group [34] was present in the spectrum in the first case and was absent in the second one.
Fig. 6Raman spectra of the initial film of hydroxide NPs synthesized via SILD at III step of the 29-th cycle and I step of the 30-th cycle.
…”
Section: Resultsmentioning
confidence: 99%